HRM and the COVID‐19 pandemic: How can we stop making a bad situation worse? - Butterick, Mark (Human Resource Management Journal, 2021)
This provocation argues that the COVID‐19 pandemic has exposed deep labour market inequalities. Partially underpinning these inequalities are human resource management (HRM) theories and practices which encourage and legitimise the commodification of labour. Workers whose jobs have been commodified have suffered disproportionately during the pandemic. While HRM is not wholly responsible for this suffering it is important for those of us involved in researching, teaching and practicing HRM to reflect on the ways in which what we do has made a bad situation worse so that we can do better in the future.